Ti/TiO2 nanotubes enhance Mycobacterium fortuitum, Mycobacterium chelonae and Mycobacterium abscessus inactivation in water - Brugnera, Michelle Fernanda [UNESP]; Miyata, Marcelo [UNESP]; Zocolo, Guilherme Juliao [UNESP]; Fujimura Leite, Clarice Queico [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Wiley-Blackwell, 2014)
BACKGROUND: Rapid-growing mycobacteria are difficult to eradicate using common disinfection practices, when compared with coliforms. They are resistant to chlorination, which is commonly used in swimming pool and drinking water treatment. They also resist treatment with glutaraldehyde (GA), benzalkonium chloride, organomercury compounds, chlorohexidine, and even autoclavation. So, the present work describes the development of a new treatment method for Mycobacterium disinfection based on phoelectrocatalytical oxidation at Ti/TiO2 nanotubes electrodes, which could be a promising alternative for its inactivation in a short treatment time.RESULTS: Nanotubular TiO2 was grown on Ti surface using electrochemical anodization in fluoride medium and applied to photoelectrocatalytic inactivation of 10(3) CFU mL(-1) Mycobaterium fortuitum, M. chelonae, and M. abscessus, which was achieved after 3 min treatment. The metabolites released during cellular lysis were also degraded with 240 min of photoelectrocatalytical treatment, as monitored by mass spectroscopy measurements. Mineralization was greater than 70% under optimum conditions. The photoelectrocatalytic method gave better results than the photolytic and photocatalytic techniques. The method provided the most efficient mycobacterial inactivation and TOC removal rate, thus being the best to disinfect mycobacterium-infected water.CONCLUSION: Photoelectrodes based on Ti/TiO2 nanotubes prepared by electrochemical anodization are a powerful alternative to disinfect mycobacterium-contaminated water. (C) 2013 Society of Chemical Industry
Keywords: photoelectrochemical disinfection; mass spectroscopy; TiO2 nanotubes; mycobacteria degradation